The Effect of Human Resources Development on the Innovation Capability of SMEs - Joseph Olubitan; Daniel Alabi; Abiola Idowu (Journal of Business & Management, 2023)
This study researched the effect of Human Resources Development as a means of improving the innovative capability of SMEs. SMEs were observed to be more innovative in their startup stage than in the developing stage (3-6 years old); hence most merged or are completely bought over by matured SMEs. Startups invest in HRD before their launch and thus bring about innovative product(s). The 21st-century business firms thrive and survive on innovation. The survival of any firm in today’s “pro-aggressive” business environment depends on how seriously it adopts an innovative culture as well as on the capability of its employees to innovate. This necessitates understanding the effect that HRD can have on the capability of SMEs to create innovative products. The research was carried out using a questionnaire survey of 50 SMEs. The population is in the Garments, Information Technology, Hospitality, Wood & Leatherworks, and other services sectors in Ibadan, Oyo State, Nigeria. While HRD variables were training, training outcomes, and training targets, the innovation capability was measured by innovation potential, innovation cycle, and new product cycle. Findings revealed that HRD plays an essential role in the innovation capability of SMEs. It was also observed that previous education, on-the-job certification, and the innovation cycle significantly affect New Product Development by SMEs.The result implies that HRD components play a pivotal role in innovative product developments by organisations and serve as an impetus to innovative capability for SMEs.